Induction of CD4(+)CD25(+)FOXP3(+) regulatory T cells during human hookworm infection modulates antigen-mediated lymphocyte proliferation. - Natasha Delaqua Ricci; Jacqueline Araújo Fiúza; Lilian Lacerda Bueno; Guilherme Grossi Lopes Cançado; Pedro Henrique Gazzinelli-Guimarães; Virgillio Gandra Martins; Leonardo Ferreira Matoso; Rodrigo Rodrigues Cambraia de Miranda; Stefan Michael Geiger; Rodrigo Correa-Oliveira; Andréa Gazzinelli; Daniella Castanheira Bartholomeu; et al. (Public Library of Science (PLoS), 2011)
Hookworm infection is considered one of the most important poverty-promoting neglected tropical diseases, infecting 576 to 740 million people worldwide, especially in the tropics and subtropics. These blood-feeding nematodes have a remarkable ability to downmodulate the host immune response, protecting themselves from elimination and minimizing severe host pathology. While several mechanisms may be involved in the immunomodulation by parasitic infection, experimental evidences have pointed toward the possible involvement of regulatory T cells (Tregs) in downregulating effector T-cell responses upon chronic infection. However, the role of Tregs cells in human hookworm infection is still poorly understood and has not been addressed yet. In the current study we observed an augmentation of circulating CD4(+)CD25(+)FOXP3(+) regulatory T cells in hookworm-infected individuals compared with healthy non-infected donors. We have also demonstrated that infected individuals present higher levels of circulating Treg cells expressing CTLA-4, GITR, IL-10, TGF-β and IL-17. Moreover, we showed that hookworm crude antigen stimulation reduces the number of CD4(+)CD25(+)FOXP3(+) T regulatory cells co-expressing IL-17 in infected individuals. Finally, PBMCs from infected individuals pulsed with excreted/secreted products or hookworm crude antigens presented an impaired cellular proliferation, which was partially augmented by the depletion of Treg cells. Our results suggest that Treg cells may play an important role in hookworm-induced immunosuppression, contributing to the longevity of hookworm survival in infected people.